Association of body pain and chronic disease: evidence from a 7-year population-based study in China. Issue 9 (7th June 2021) - Luo, Yaxin; Liu, Zheran; Yang, Lianlian; Li, Juejin; Zhang, Qiang; Peng, Xingchen; Hu, Xiaolin
Abstract : Background: Evidence is limited on the risk impact of body pain on future chronic disease. The present study aimed to investigate the association between body pain and chronic diseases. Methods: Data were analyzed using four waves of the China Health and Retirement Longitudinal Study with 17 708 individual respondents aged 45 years and older. The association between body pain and chronic disease was estimated in both a cross-sectional cohort (2011) and a longitudinal cohort (2011–2018). The key outcomes include the incidence of overall and any specific chronic diseases. The associations among different body pain sites and 10 independent chronic disease risks were also assessed. Findings: A total of 17 128 participants in 2011 were included in the cross-sectional cohort and 5611 participants were included in the 2011–2018 longitudinal cohort. Body pain showed an association with overall chronic disease in both the cross-sectional models (OR 2.71, 95% CI 2.47 to 2.98) and longitudinal model (risk ratio (RR) 1.21, 95% CI 1.07 to 1.35). Moreover, body pain was found to be associated with an increased risk of chronic respiratory disease (RR 1.43, 95% CI 1.06 to 1.92), heart disease (RR 1.45, 95% CI 1.12 to 1.89), kidney disease (RR 1.83, 95% CI 1.28 to 2.6), and digestive disease (RR 1.48, 95% CI 1.17 to 1.88). Conclusion: Body pain is associated with major disease and mortality. Future clinical research should be targeted to whether or not improved pain control can mitigate this population-level disease burden.